Mouths of Roanoke River, North Carolina / Triangulation and topography by R.E. Halter, Sub-Assist. Hydrography by J.S. Bradford, Sub-Assist. acting under orders of Actg. Rear Admiral S.P. Lee, U.S. Navy, Comdg. North Atlantic Blockading Squadron - United States Coast Survey (Washington, D.C. : United States Coast Survey, 1864)
(Date of first publication 1864) "No. 409 price 10 cents" and "Plate no. 983" are printed in the upper margin General chart indicating soundings and bottom contour at 12 feet Grayscale 1:30,000